Juridical Review of Restorative Justice in The Case of Criminal Negligence Causing Death in The Gianyar Resort Police - Hendra, I Made Julia; Made Subawa; Siti Nurmawan Damanik (International Journal of Contemporary Sciences (IJCS), 2024)
In Article 5 and Article 6 of the Regulation of the Chief of Police of the Republic of Indonesia Number 8 of 2021 concerning Handling Crimes Based on Restorative Justice, some conditions must be met for a case to be resolved through restorative justice. This regulation emphasizes that not all criminal acts can be resolved through restorative justice. Settlement through restorative justice is not necessarily able to eliminate or stop an investigation and/or investigation in the Police, especially against article 359 of the Criminal Code because legal norms are blurring. for example, in the case of the Ayuterra Resort Owner and the Contractor, can be interpreted as who is most responsible for the breaking of the elevator / Inclinator rope which caused the death of 5 (five) employees because in one criminal event, it is not possible that both can be used as Criminal Offenders. Obstacles in the application of restorative justice experienced by the investigators of the Gianyar Resort Police on the crime of negligence that caused death, among others: There is no common perception of the application of articles 359 on negligence causing death among law enforcement officials regarding the handling of restorative justice for the best interests of the perpetrators of criminal acts of negligence causing death